Economic Dictionaries on the Web - Besomi, Daniele (HERMES - Journal of Language and Communication in Business, 2013)
This paper surveys the economic dictionaries available on the internet, both for free and on subscription, addressed to various kinds of audiences from schoolchildren to research students and academics. The focus is not much on content, but on whether and how the possibilities opened by electronic editing and by the modes of distribution and interaction opened by the internet are exploited in the organization and presentation of the materials. The upshot is that although a number of web dictionaries have taken advantage of some of the innovations offered by the internet (in particular the possibility of regularly updating, of turning cross-references into hyperlinks, of adding links to external materials, of adding more or less complex search engines), the observation that internet lexicography has mostly produced more ef! cient dictionary without, however, fundamentally altering the traditional paper structure can be con! rmed for this particular subset of reference works. In particular, what is scarcely explored is the possibility of visualizing the relationship between entries, thus abandoning the project of the early encyclopedists right when the technology provides the means of accomplishing it.